Geodynamic Zoning For Underground Isolation Of Radioctive Waste (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The problem of area selection for underground isolation of radioactive waste is important for all countries using nuclear power. The paper presents the results of modeling the stress-deformed state of Nizhnekanskiy granitoid massif and shows the possibility of using such simulations for the geodynamic zoning of areas. The calculation is given to the most probable directions of groundwater filtration, which is one of the main threats for the nuclear waste repository.